2019
DOI: 10.1111/nph.16232
|View full text |Cite
|
Sign up to set email alerts
|

A transcription factor OsbHLH156 regulates Strategy II iron acquisition through localising IRO2 to the nucleus in rice

Abstract: Summary Plants have evolved two strategies to acquire ferrous (Strategy I) or ferric (Strategy II) iron from soil. The iron‐related bHLH transcription factor 2 (IRO2) has been identified as a key regulator of iron acquisition (Strategy II) in rice. However, its mode of action, subcellular localisation and binding partners are not clearly defined. Using RNA‐seq analyses, we identified a novel bHLH‐type transcription factor, OsbHLH156. The function of OsbHLH156 in Fe homeostasis was analysed by characterisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 48 publications
2
75
2
Order By: Relevance
“…OsIRO2 is preferentially expressed in the cytoplasm, and the upregulated expression of OsFIT results in the increased nuclear accumulation of OsIRO2 (Figure 2C). A similar result was also reported by Wang et al (2020). A latest study found that AtFIT promotes the nuclear accumulation of AtbHLH39, an Arabidopsis homolog of OsIRO2, in Arabidopsis (Trofimov et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…OsIRO2 is preferentially expressed in the cytoplasm, and the upregulated expression of OsFIT results in the increased nuclear accumulation of OsIRO2 (Figure 2C). A similar result was also reported by Wang et al (2020). A latest study found that AtFIT promotes the nuclear accumulation of AtbHLH39, an Arabidopsis homolog of OsIRO2, in Arabidopsis (Trofimov et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, Arabidopsis bHLH IVc TFs promote the nuclear accumulation of AtbHLH121 which is required for the maintenance of Arabidopsis Fe homeostasis (Kim et al, 2019; Gao et al, 2020; Lei et al, 2020). Although we did not observe the localization change of OsIRO2 in response to Fe deficiency in our transient expression assays, the increased nuclear accumulation of OsIRO2 under Fe deficiency condition was observed by Wang et al (2020). Further investigations are required to reveal the biological relevance of OsIRO2 localization change with the Fe deficiency response.…”
Section: Discussioncontrasting
confidence: 54%
“…A recent study in rice identified OsbHLH156 as a rice ortholog of FIT, albeit with low sequence similarity and controlling Strategy II, instead of Strategy I, Fe uptake. Interestingly, this transcription factor was found necessary for the nuclear localization of OsIRO2, the rice ortholog of bHLH039 (Wang et al, ). This underlines the importance of the here described phenomenon in Arabidopsis as an integral part of the plant Fe deficiency response.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Wang et al (2020) also reported the function of OsbHLH156/OsFIT in rice. Here, we not only characterizes the biological role of OsFIT and OsIRO2 and their genetic relationship in Fe homeostasis, but also reveals their molecular regulation mechanism.…”
Section: Introductionmentioning
confidence: 96%